Alpha decay of excited states of carbon-12 - Shackleton, David (University of Cape Town, 2016)
A crystal of the carbon-rich phosphor, anthracene, has been bombarded by monoenergetic fast neutrons. Alpha-particle decays of carbon nuclei have been separated from other events by a specialised application of the pulse shape discrimination technique. A numerical analysis of the data has yielded alpha-particle energy spectra over a wide energy range. A counter has been assembled to detect neutrons scattered by carbon nuclei in the crystal, and the measurements repeated in coincidence with these neutrons. The energy range of particle resolving power has been extended. Structure in the resulting alpha-particle and proton energy spectra is attributed to particle decays of specific levels in carbon-12. It is shown how the experiment may be modified and extended to measure decay parameters in absolute terms.